ART AS SCREEN BETWEEN SOUL AND WORLD - DOES CREATIVE PERSONALITY GROW ON INNER VALUE? - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2023)
This essay investigates the relation between soul and Art,and delves into personality and social context, the two- starting premisses of ANTOA. This new theory based on five markers in total, of which the fifth item, message, symbol and value, is also taken care of. As tool of consideration. Is Art indeed an ominous screen, a special gauze thru which the soul peeps at the outside world? Can we use ANTOA to attach meaning to a soulful rendition of inventive, immersive, and imaginative activity? The latter furthermore establishing a set of social relations, discussing the inter-relational affairs in a given social net. That reels off in a certain geographical region with socio-political and linguistic preferences. While freedom of speech and symbolic dialect need defending, very little reflection takes place. An abstract painting of no meaning becomes a creator of social webs? Of an invisible yet closely knit social fabric around us? I then ask if such a screen or filter, identified as divider between soul and world, can be detected, exposed, and verified in terms of the 5 pointer ANTOA countdown? So that after sensible enquiry we may speak of relevant, up-to-date, and sincere creativity. These tentative indicators elucidate the anthropological approach: How does Art create and boost that net of human relations? Can these relations be traced to a family or ethnic group environment, and how does Art apply its controversial freak outsider element to the division between inner readings and outside text? And does this amazing filter or curtain deliver new values? So that we can open the barrier and step from indeterminate to fully graspable? In spite of recognizing a hazy area beyond the screen that may be at odds with a clear view. Can the psychological function save us and serve as motivator and inventor? Who both penetratethe membranes of the creative soul, stacked sky-high like the compressed pages of a thick guidebo k. As trigger for the investigation, I had comeacross a highly informative outline of the English school of painting from 1683 to 1901 and unearthed the soulful element in the prophetic activities of the Pre-Raphaelites Brotherhood - PRB. That even impressed French artists at mid-19th century salons across the channel in Paris! The essay ends with assessing my theory in terms of history of Art and an often overlooked but valid link between social relations and creative context. The latter similar to a deep well of soulful imagination.